9k+16+2k=15k+89-6k

Simple and best practice solution for 9k+16+2k=15k+89-6k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9k+16+2k=15k+89-6k equation:



9k+16+2k=15k+89-6k
We move all terms to the left:
9k+16+2k-(15k+89-6k)=0
We add all the numbers together, and all the variables
9k+2k-(9k+89)+16=0
We add all the numbers together, and all the variables
11k-(9k+89)+16=0
We get rid of parentheses
11k-9k-89+16=0
We add all the numbers together, and all the variables
2k-73=0
We move all terms containing k to the left, all other terms to the right
2k=73
k=73/2
k=36+1/2

See similar equations:

| e-12=-9 | | 78-v=203 | | 5x=-625 | | f−6=f+8 | | 18=10x-x | | -10+x=x+22 | | x-7/2=12 | | 3x-7(3x-3)=-105 | | 63=3u+4u | | 2x*2x*2x*2x=8x | | {28}{2x+3}=4 | | -3w=20 | | 8x-7+1x+10+2x+12=180 | | {5x+2}{7}={2x}{7}+2 | | 8z=9z-6 | | 1/12x^2+1/3x+1/4=0 | | 4+6u=5u | | 7x+36=4x-54 | | 1/12x^2+1/3x1/4=0 | | {5x+2}={7}{2x}{7}+2 | | 4/7x-2=2/7x-4 | | 6-7h=-6h | | 17/11=y/12 | | 180=(2x-4)+(180-(2x-4)) | | 4/2x+4=5/3x-2 | | 7x-36=4x=54-36 | | 2x=-5+7+11 | | 11x-4+11x-4=80 | | 2(4x−11)=10. | | 28/2x+3=4 | | -5=v+5-3v | | 4x-12=2×-6 |

Equations solver categories